PENERAPAN TEORI PERILAKU TERENCANA PADA MAHASISWA YANG TERGABUNG PADA KOMUNITAS KEWIRAUSAHAAN - Agustina, Tri Siwi (Universitas Nahdlatul Ulama Surabaya, 2021)
The younger generation still had enough time to be able to determine the best career for their life, including being able to choose his career as an entrepreneur. This study focused on students belonging to the entrepreneurial community in the campus therefore an object of research is the students belonging to the entrepreneurial community WEBS and BETA at Airlangga University. This study uses Partial Least Square (PLS) as a statistical test to answer the problem formulation and testing hypotheses based on the study of theory and previous research. The sample used in this study using census sampling methods, which uses the entire population as a sample in the study. The samples used in the study were 80 students in the WEBS membership and BETA membership in Airlangga University. Method of data dissemination is done with a questionnaire during March until April, 2019. The result shows that (1) Educational support, subjective norm, and structural support directly influence the entrepreneurial intention; (2) Educational support and structural support indirectly influncing on entrepreneurial intention through attitude toward entrepreneurial behavior and perceived behavioral control; (3) Subjective norms indirectly influncing on entrepreneurial intention through attitude toward entrepreneurial behavior, but Subjective norms can’t influencing entrepreneurial intention through perceived behavioral control.